Economic and financial determinants of bankrupcy: evidence from Ecuador’s private banks and the impact of dollarization on financial fragility - Uquillas, Adriana; Flores, Francis (Review of Business Management, 2020)
Purpose – An econometric model is established to explain bankruptcy in Ecuadorian banks. The utility of combining macroeconomic, financial, and idiosyncratic determinants to explain bankruptcy is empirically demonstrated. Design/methodology/approach – The cross-sectional analysis includes 24 banks between 1996 and 2016. Bankruptcy is considered as a rare event. Findings – Even in adverse macroeconomic conditions, the main factor explaining bankruptcy is lax administration. Also, those banks with higher levels of indebtedness with respect to their capital levels are more susceptible to bankruptcy. Higher levels of spread and lower inflation are associated with lower levels of bankruptcy. Ceteris paribus, after dollarization the bankruptcy probability decreases and the effective management of each bank becomes a relevant factor to explain bankruptcy. Originality/value – Different determinants are combined in order to produce predictive models with practical value and macro-dependent dynamics that are relevant for stress tests. There is empirical evidence that the change in the monetary system has helped to stabilize the financial system. The problem of having a small sample and rare events is evident and adequately addressed.